Tantangan Partisipasi Pemilih Pemula dalam Penyelenggaraan Pemilu Serentak Tahun 2024 di Kota Bima - Nabil Fajaruddin; Taufik Firmanto; Aman Ma'arij (Jurnal Hukum Lex Generalis, 2025)
This study examines the level of participation of first-time voters in the 2024 Simultaneous Elections in Bima City, a strategic group in determining the nation's political direction. Based on legal, sociological, and philosophical approaches, it was found that first-time voter involvement is still influenced by a lack of political education, family factors, and the influence of social media. This study suggests the need to strengthen political education and the active role of educational institutions and the regional General Elections Commission (KPU). Bima City was chosen as the research location because it has a significant number of first-time voters and quite complex local political dynamics, making it representative in describing the political participation of the younger generation.